Efeito de um programa multiprofissional de tratamento da obesidade sobre o estágio de prontidão para mudança de comportamento de adolescentes - Santos, Tamires Leal Cordeiro dos (2018)
Abstract: The prevalence of obesity has reached epidemic proportions, becoming a serious health problem worldwide, especially among adolescents. The multiprofessional treatment based on cognitive-behavioral therapy has been indicated as an efficient method to treat this comorbidity, being important the evaluation of the stage of readiness to change of behavior (EPMC), which allows to identify the readiness in which the individual is for change. Objectives: The objective of this study was to identify the EPMC of adolescents enrolled in a Multiprofessional Obesity Treatment Program (PMTO / NEMO / UEM), to verify if there is a relationship between EPMC for Physical Activity (PA) and Cardiorespiratory Fitness (CRF) as well as to analyze if possible differences in the stages are related to Sex. In the original article II, the objective was to verify the effects of a PMTO on teenagers' PMCT. Original article I presents a cross-sectional design with 164 overweight adolescents entering a PMTO. The original article II is a pragmatic clinical trial, with 164 adolescents in the Intervention Group (GI) and 40 in the Control Group (CG). The EPMC was assessed using the Stage of Change (SOC) questionnaire. Data normality was tested using the Kolmogorov-Smirnov (GI) and Shapiro Wilk (GC) tests. When the normality of the data was confirmed, the paired t-test was used for comparisons between moments and independent t for comparisons between groups, and the non-normal data were used the Wilcoxon or U test of Mann-Whitney. The chi-square test was used to verify the association between the classifications with the age group, degree of overweight and cardiorespiratory fitness, and differences between the sexes. Spearman's correlation was used to verify the relationship between active and inactive behaviors according to the EPMC-PA and the CRF classification. The analysis of variance (ANOVA) for repeated measurements was used to compare the global EPMC score of adolescents between the groups (GI and GC) at different times (pre and post 16 weeks). The Bonferroni post hoc test was used to identify the specific differences in the variables in which the F values found were higher than the established statistical significance criterion (p <0.05). The data were processed in the SPSS 20.0 IMB package. Mean age was 15.7 ± 0.7 years, BMI 31.9 ± 5.4 kg / m2. and girls accounted for more than half of the study sample (60%). When they entered the PMTO, most of the adolescents were identified in the preparation stage and the minority in the maintenance stage, both for EPMC-global (49.4%) and EPMC-PA (38.4%). Statistically significant differences were also found in the readiness for behavioral changes in boys and girls (p = 0.024), and EPMC-PA did not correlate well with adolescent RTA (r = 0.200). The PMTO was effective in providing improvements in all domains that make up the EPMC (p <.001). The overall GI and GC did not differ at the pre-time point, however, after 16 weeks, only GI showed statistically significant changes, exhibiting a statistically significant interaction (F (1.181) = 56.3, p = 0.001). At the moment post PMTO, in the domains of fruit and vegetable consumption, physical activity and global EPMC, there were no adolescents classified in the pre-contemplation stage. Pre-intervention most adolescents were in the preparation stage, and after 16 weeks, in the stage of action for all domains. The 16-week PMTO was effective in providing behavioral changes at the global level related to eating habits and practice of PA in overweight adolescents, as well as significant changes in the body and anthropometric composition of these adolescents. Thus, the EPMC evaluation is relevant in programs focused on the treatment of obesity, since this evaluation allows the follow-up of the behavior change processes promoted by the treatment and if the subjects have become inclined to include such changes in your usual routine